A comprehensive review of prioritised interventions to improve the health and wellbeing of persons with lived experience of homelessness. Issue 2 (24th June 2021) - Moledina, Aliza; Magwood, Olivia; Agbata, Eric; Hung, Jui‐Hsia; Saad, Ammar; Thavorn, Kednapa; Salvalaggio, Ginetta; Bloch, Gary; Ponka, David; Aubrey, Tim; Kendall, Claire; Pottie, Kevin
Abstract: Background: Homelessness has emerged as a public health priority, with growing numbers of vulnerable populations despite advances in social welfare. In February 2020, the United Nations passed a historic resolution, identifying the need to adopt social‐protection systems and ensure access to safe and affordable housing for all. The establishment of housing stability is a critical outcome that intersects with other social inequities. Prior research has shown that in comparison to the general population, people experiencing homelessness have higher rates of infectious diseases, chronic illnesses, and mental‐health disorders, along with disproportionately poorer outcomes. Hence, there is an urgent need to identify effective interventions to improve the lives of people living with homelessness. Objectives: The objective of this systematic review is to identify, appraise, and synthesise the best available evidence on the benefits and cost‐effectiveness of interventions to improve the health and social outcomes of people experiencing homelessness. Search Methods: In consultation with an information scientist, we searched nine bibliographic databases, including Medline, EMBASE, and Cochrane CENTRAL, from database inception to February 10, 2020 using keywords and MeSH terms. We conducted a focused grey literature search and consulted experts for additional studies. Selection Criteria: Teams of two reviewers independently screened studies against our inclusion criteria. We included randomised control trials (RCTs) and quasi‐experimental studies conducted among populations experiencing homelessness in high‐income countries. Eligible interventions included permanent supportive housing (PSH), income assistance, standard case management (SCM), peer support, mental health interventions such as assertive community treatment (ACT), intensive case management (ICM), critical time intervention (CTI) and injectable antipsychotics, and substance‐use interventions, including supervised consumption facilities (SCFs), managed alcohol programmes and opioid agonist therapy. Outcomes of interest were housing stability, mental health, quality of life, substance use, hospitalisations, employment and income. Data Collection and Analysis: Teams of two reviewers extracted data in duplicate and independently. We assessed risk of bias using the Cochrane Risk of Bias tool. We performed our statistical analyses using RevMan 5.3. For dichotomous data, we used odds ratios and risk ratios with 95% confidence intervals. For continuous data, we used the mean difference (MD) with a 95% CI if the outcomes were measured in the same way between trials. We used the standardised mean difference with a 95% CI to combine trials that measured the same outcome but used different methods of measurement. Whenever possible, we pooled effect estimates using a random‐effects model. Main Results: The search resulted in 15, 889 citations. We included 86 studies (128 citations) that examined the effectiveness and/or cost‐effectiveness of interventions for people with lived experience of homelessness. Studies were conducted in the United States (73), Canada (8), United Kingdom (2), the Netherlands (2) and Australia (1). The studies were of low to moderate certainty, with several concerns regarding the risk of bias. PSH was found to have significant benefits on housing stability as compared to usual care. These benefits impacted both high‐ and moderate‐needs populations with significant cimorbid mental illness and substance‐use disorders. PSH may also reduce emergency department visits and days spent hospitalised. Most studies found no significant benefit of PSH on mental‐health or substance‐use outcomes. The effect on quality of life was also mixed and unclear. In one study, PSH resulted in lower odds of obtaining employment. The effect on income showed no significant differences. Income assistance appeared to have some benefits in improving housing stability, particularly in the form of rental subsidies. Although short‐term improvement in depression and perceived stress levels were reported, no evidence of the long‐term effect on mental health measures was found. No consistent impact on the outcomes of quality of life, substance use, hospitalisations, employment status, or earned income could be detected when compared with usual services. SCM interventions may have a small beneficial effect on housing stability, though results were mixed. Results for peer support interventions were also mixed, though no benefit was noted in housing stability specifically. Mental health interventions (ICM, ACT, CTI) appeared to reduce the number of days homeless and had varied effects on psychiatric symptoms, quality of life, and substance use over time. Cost analyses of PSH interventions reported mixed results. Seven studies showed that PSH interventions were associated with increased cost to payers and that the cost of the interventions were only partially offset by savings in medical‐ and social‐services costs. Six studies revealed that PSH interventions saved the payers money. Two studies focused on the cost‐effectiveness of income‐assistance interventions. For each additional day housed, clients who received income assistance incurred additional costs of US$45 (95% CI, −$19, −$108) from the societal perspective. In addition, the benefits gained from temporary financial assistance were found to outweigh the costs, with a net savings of US$20, 548. The economic implications of case management interventions (SCM, ICM, ACT, CTI) was highly uncertain. SCM clients were found to incur higher costs than those receiving the usual care. For ICM, all included studies suggested that the intervention may be cost‐offset or cost‐effective. Regarding ACT, included studies consistently revealed that ACT saved payers money and improved health outcomes than usual care. Despite having comparable costs (US$52, 574 vs. US$51, 749), CTI led to greater nonhomeless nights (508 vs. 450 nights) compared to usual services. Authors' Conclusions: PSH interventions improved housing stability for people living with homelessness. High‐intensity case management and income‐assistance interventions may also benefit housing stability. The majority of included interventions inconsistently detected benefits for mental health, quality of life, substance use, employment and income. These results have important implications for public health, social policy, and community programme implementation. The COVID‐19 pandemic has highlighted the urgent need to tackle systemic inequality and address social determinants of health. Our review provides timely evidence on PSH, income assistance, and mental health interventions as a means of improving housing stability. PSH has major cost and policy implications and this approach could play a key role in ending homelessness. Evidence‐based reviews like this one can guide practice and outcome research and contribute to advancing international networks committed to solving homelessness.